High-Resolution Wellbore Temperature Logging Combined with a Borehole-Scale Heat Budget: Conceptual and Analytical Approaches to Characterize Hydraulically Active Fractures and Groundwater Origin - Guillaume Meyzonnat; Florent Barbecot; José A. Corcho-Alvarado; Antoine Tognelli; Hermann Zeyen; Alexandra Mattei; Renald McCormack (Geofluids)
This work aims to provide an overview of the thermal processes that shape wellbore temperature profiles under static and dynamic conditions. Understanding of the respective influences of advection and conduction heat fluxes is improved through the use of a new heat budget at the borehole scale. Keeping in mind the thermal processes involved, a qualitative interpretation of the temperature profiles allows the occurrence, the position, and the origin of groundwater flowing into wellbores from hydraulically active fractures to be constrained. With the use of a heat budget developed at the borehole scale, temperature logging efficiency has been quantitatively enhanced and allows inflow temperatures to be calculated through the simultaneous use of a flowmeter. Under certain hydraulic or pumping conditions, both inflow intensities and associated temperatures can also be directly modelled from temperature data and the use of the heat budget. Theoretical and applied examples of the heat budget application are provided. Applied examples are shown using high-resolution temperature logging, spinner flow metering, and televiewing for three wells installed in fractured bedrock aquifers in the St-Lawrence Lowlands, Quebec, Canada. Through relatively rapid manipulations, thermal measurements in such cases can be used to detect the intervals or discrete positions of hydraulically active fractures in wellbores, as well as the existence of ambient flows with a high degree of sensitivity, even at very low flows. Heat budget calculations at the borehole scale during pumping indicate that heat advection fluxes rapidly dominate over heat conduction fluxes with the borehole wall. The full characterization of inflow intensities provides information about the distribution of hydraulic properties with depth. The full knowledge of inflow temperatures indicates horizons that are drained from within the aquifer, providing advantageous information on the depth from which groundwater originates during pumping.